Adaptive Resistance to an Inhibitor of Chromosomal Instability in Human Cancer Cells - Bernardo Orr; Lama Talje; Zhexian Liu; Benjamin H. Kwok; Duane A. Compton (Cell Reports, 2016)
Karyotype diversity is a hallmark of solid tumors that contributes to intratumor heterogeneity. This diversity is generated by persistent chromosome mis-segregation associated with chromosomal instability (CIN). CIN correlates with tumor relapse and is thought to promote drug resistance by creating a vast genomic landscape through which karyotypically unique clones survive lethal drug selection. We explore this proposition using a small molecule (UMK57) that suppresses chromosome mis-segregation in CIN cancer cells by potentiating the activity of the kinesin-13 protein MCAK. Sublethal doses of UMK57 destabilize kinetochore-microtubule (k-MT) attachments during mitosis to increase chromosome segregation fidelity. Surprisingly, chromosome mis-segregation rebounds in UMK57-treated cancer cells within a few days. This rapid relapse is driven by alterations in the Aurora B signaling pathway that hyper-stabilize k-MT attachments and is reversible following UMK57 removal. Thus, cancer cells display adaptive resistance to therapies targeting CIN through rapid and reversible changes to mitotic signaling networks.